Actualization of Pesantren Values in the Practice of Fatherly Leadership at Raudhatul Athfal - Novan Ardy Wiyani; Wan-Alawee Samaeng (MUWAZAH : jurnal kajian gender, 2022)
The purpose of this study is to describe and analyze the actualization of the values of pesantren in the practice of fatherly leadership at RA Al Ma'arif NU Plompong. This research is a natural qualitative research. Data were collected by interview, observation, and documentation. Then the data were analyzed using the Miles and Huberman model data analysis technique which consisted of data reduction, data display and verification. The results showed that the head of RA Al Ma'arif NU Plompong actualized four pesantren values that had relevance to the nature of fatherly leadership, namely authoritarian, charismatic, and participatory-collaborative values. Authoritarian values are actualized by making PAUD policies and PAUD service programs. Charismatic value is shown by being a good role model. Then he showed the value of participatory-collaborative by intensely assisting and assisting teachers in their work. The actualization of pesantren values in the practice of fatherly leadership has implications for the creation of a family atmosphere between leaders and teachers which makes teachers have a strong commitment to advancing the institution.